A Study on the Performance and Risk-Return Characteristics of the Hedge Fund Industry - Hamza, Noormohamed (2012)
This study aims to investigate the performance of hedge funds and their risk-return characteristics and benefits. We will investigate the possible diversification benefits of hedge funds as returns have shown too often to have low correlations with other financial assets and they also are said to offer higher returns for comparatively lower risk. Thus, we will use regression analysis to determine the hedge fund industries relation with our market proxy, the S&P 500. Performance ratios and other statistical methods are used to evaluate the industry further. The results show that there is evidence of the value added by hedge funds and their performance does indeed make them beneficial in risk diversification for portfolios. However, the results are less conclusive because of the biases that are inherent in the data and in the industry as a whole.